1986
DOI: 10.1073/pnas.83.20.7658
|View full text |Cite
|
Sign up to set email alerts
|

Availability of chemosensory receptors is down-regulated by habituation of larvae to a morphogenetic signal.

Abstract: Larvae of the gastropod mollusc Haliotis rufescens are induced to settle from the plankton and metamorphose in response to exogenous y-aminobutyric acid (GABA) and a number of GABA-mimetic compounds, including a GABA-mimetic inducer uniquely associated with the surfaces of the naturally recruiting algae. Previous evidence has shown that recognition of these inducers is mediated by specialized chemosensory receptors on the larval epithelium and that transduction of the morphogenetic signal then is mediated by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 27 publications
4
43
1
Order By: Relevance
“…It induces metamorphosis in Haliotis by mimicking the actions of the natural inducer at external chemoreceptors (Trapido-Rosenthal and Morse, 1985Morse, , 1986aBarlow, 1990;Wodicka and Morse, 1991). Injection of GABA provided a negative control for our study.…”
Section: Discussionmentioning
confidence: 99%
“…It induces metamorphosis in Haliotis by mimicking the actions of the natural inducer at external chemoreceptors (Trapido-Rosenthal and Morse, 1985Morse, , 1986aBarlow, 1990;Wodicka and Morse, 1991). Injection of GABA provided a negative control for our study.…”
Section: Discussionmentioning
confidence: 99%
“…rufescens (red abalone) larvae were produced and reared as described (1,2,4,7). Assays were performed in duplicate at 15'C in glass vials containing =200 fully competent larvae (9 days old) in a final vol of 10 ml of fresh 5-,um-filtered ultraviolet-sterilized seawater, with rifampicin at 2 pkg/ml, and other compounds at the indicated concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…The settlement and metamorphosis of Haliotis larvae in response to low concentrations of any of these inducers can be facilitated, or amplified, by several diamino acids structurally related to lysine, including L-a,3-diaminopropionic acid (DAPA) (see Fig. 1A), without altering the number or affinity of the GABA chemoreceptors (6)(7)(8).Recent evidence has shown that this facilitation of the morphogenetic response occurs at a postreceptor level independent of inducer binding at the GABA chemoreceptors (6). We present evidence here that transduction of the facilitating DAPA signal is mediated by a regulatory pathway that is separate from the morphogenetic pathway.…”
mentioning
confidence: 99%
“…These authors have observed that a decrease in external potassium concentration inhibits induction by GABA, which could be due to hyperpolarization and which would antagonize the depolarization mediated by GABA. The activation of anionic channels would depend on enzymes phosphorylated by protein kinases A, which would, In turn, be activated by cAMP (Morse et al 1980, Trapido-Rosenthal & Morse 1986b. The levels of the latter would be increased by the activation of the adenylate cyclase through the binding of the exoyenoils liya~~ci jillductllj iu tile recepior jMorse i93i).…”
Section: Choline Derivativesmentioning
confidence: 99%